Comparative Study of Three Phase Grid Connected Photovoltaic Inverter Using PI and Fuzzy Logic Controller with Switching Losses Calculation - M. Venkatesan; R. Rajeshwari; N. Deverajan; M. Kaliyamoorthy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
A comparative study of three phase grid connected photovoltaic (PV) inverter using Proprotional Controller (PI) and Fuzzy Logic Controller (FLC) is presented in this paper. Proposed three phase inverter with single DC source employing three phase transformer for grid connected PV system controlled by using Space Vector Pulse Width Modulation (SVPWM) technique.  PI and FLC are used as current controller for regulating the current. Perturb and observe Maximum Power Point Technique (MPPT) is used for tracking of maximum power from the PV panel. Finally Total Harmonic Distortion (THD) comparison made between two controllers for validation of results. Furthermore swithing losses of inverter are also presented. The simulation results are obtained using MATLAB simulink.